Making use of data for assessments: harnessing analytics and data science - Ifenthaler, D.; Greiff, S.; Gibson, David (Springer, 2018)
The increased availability of vast and highly varied amounts of data from learners, teachers, learning environments, and administrative systems within educational settings is overwhelming. The focus of this chapter is on how data with a large number of records, of widely differing datatypes, and arriving rapidly from multiple sources can be harnessed for meaningful assessments and supporting learners in a wide variety of learning situations. Distinct features of analytics-driven assessments may include self-assessments, peer assessments, and semantic rich and personalized feedback as well as adaptive prompts for reflection. The chapter concludes with future directions in the broad area of analytics-driven assessments for teachers and educational researchers.